A test of the survival processing advantage in implicit and explicit memory tests. - McBride, Dawn; Thomas, Brandon; Zimmerman, Corinne (Memory & Cognition, 2013)
The present study was designed to investigate the survival processing effect (Nairne, Thompson, & Pandeirada, Journal of Experimental Psychology: Learning, Memory, and Cognition, 33, 263-273, ) in cued implicit and explicit memory tests. The survival effect has been well established in explicit free recall and recognition tests, but has not been evident in implicit memory tests or in cued explicit tests. In Experiment 1 of the present study, we tested implicit and explicit memory for words studied in survival, moving, or pleasantness contexts in stem completion tests. In Experiment 2, we further tested these effects in implicit and explicit category production tests. Across the two experiments, with four separate memory tasks that included a total of 525 subjects, no survival processing advantage was found, replicating the results from implicit tests reported by Tse and Altarriba (Memory & Cognition, 38, 1110-1121, ). Thus, although the survival effect appears to be quite robust in free recall and recognition tests, it has not been replicated in cued implicit and explicit memory tests. The similar results found for the implicit and explicit tests in the present study do not support encoding elaboration explanations of the survival processing effect.